MENGGALI POTENSI KREATIVITAS KEWIRAUSAHAAN MAHASISWA MELALUI BAZAR INOVASI - Rezky Tania; Susan Febriyanti; Rozalia Rozalia; Karyadi Hidayat (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
The innovation bazaar is an effective contextual learning strategy for fostering students' creativity, innovation, and entrepreneurial spirit. Through this activity, students not only learn entrepreneurial theory but also gain hands-on experience in managing business ideas, marketing products, and interacting with the campus community. This initiative aims to explore students' creative and innovative potential through the innovation bazaar. The implementation method involves students in the planning, implementation, and evaluation of the innovation bazaar. Results indicate that the innovation bazaar enhances students' creative thinking skills, communication skills, teamwork skills, and self-confidence in developing innovative business ideas. Furthermore, this activity fosters a sense of responsibility and independence within the context of project-based learning. Therefore, the innovation bazaar can serve as an effective learning medium for integrating entrepreneurial values ​​into students.